2020
DOI: 10.1103/physrevb.101.100506
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative theory of triplet pairing in the unconventional superconductor LaNiGa2

Abstract: The exceptionally low-symmetry crystal structures of the time-reversal symmetry breaking superconductors LaNiC2 and LaNiGa2 lead to an internally-antisymmetric non-unitary triplet (INT) state as the only possibility compatible with experiments. We argue that this state has a distinct signature: a double-peak structure in the Density of States (DOS) which resolves in the spin channel in a particular way. We construct a detailed model of LaNiGa2 capturing its electronic band structure and magnetic properties ab … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 56 publications
(86 reference statements)
0
41
0
Order By: Relevance
“…[15,16]. It has already been shown to effectively describe gap anisotropy [13] and impurity scattering [14], along with complex superconducting order parameters in LaNiC2 [21] and LaNiGa2 [22]. Within the nonrelativistic theory the densities are given by ρ(r) =ρ ↑ (r) + ρ ↓ (r), ( 4)…”
Section: Methodsmentioning
confidence: 99%
“…[15,16]. It has already been shown to effectively describe gap anisotropy [13] and impurity scattering [14], along with complex superconducting order parameters in LaNiC2 [21] and LaNiGa2 [22]. Within the nonrelativistic theory the densities are given by ρ(r) =ρ ↑ (r) + ρ ↓ (r), ( 4)…”
Section: Methodsmentioning
confidence: 99%
“…In the case of LaNiC 2 , it was shown that the breaking of TRS at T c is incompatible with a significant influence of ASOC [18]. Moreover, the occurrence of TRS breaking together with two-gap superconductivity in both LaNiC 2 [19], as well as centrosymmetric LaNiGa 2 [20,21], was accounted for by an even-parity nonunitary triplet pairing state [21,22]. Furthermore, the recent findings of the signatures of TRS breaking in centrosymmetric elemental rhenium also suggests that broken inversion symmetry is not essential for this phenomenon in Re-based superconductors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, for the magnetic Josephson junctions, the relative orien-tation of two d-vectors in STSs can be used to adjust the Andreev bound states 24 and to produce the Josephson current switches 25 or the 0-π phase transitions 26,27 valuable for the circuit element of quantum computation 28 . For the material realization of STSs, there are many theoretical and experimental researches for the identification of the spin-triplet pairing 18,[29][30][31] , which include the determination of the direction of the d-vector 32,33 . In addition, the spin-triplet pairing with a nonzero d-vector also appears in some superconducting material with the spin-orbit coupling.…”
Section: Introductionmentioning
confidence: 99%